2017
DOI: 10.1007/s10815-017-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal polymorphisms are independently associated with multinucleated embryo formation

Abstract: Chromosomal polymorphisms were independently associated with multinucleation embryo formation. A higher LH level on the day of HCG triggering was associated with a decreased chance of multinucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
2
7
1
Order By: Relevance
“…Then, the PGT data were analyzed for CTCPM carriers and CT carriers. Embryo development suggests that CPM is associated with multinucleated embryo formation (Sun et al, 2018) and has an impact on fertilization rate, embryo cleavage rate, high-quality embryo rate, and live birth rate (Liang et al, 2014;Ou et al, 2019). However, in our data, there was no statistical difference in fertilization rate, cleavage rate on Day 3, blastocysts rate, or highquality blastocyst rate between CPM carriers and patients with normal chromosomes.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Then, the PGT data were analyzed for CTCPM carriers and CT carriers. Embryo development suggests that CPM is associated with multinucleated embryo formation (Sun et al, 2018) and has an impact on fertilization rate, embryo cleavage rate, high-quality embryo rate, and live birth rate (Liang et al, 2014;Ou et al, 2019). However, in our data, there was no statistical difference in fertilization rate, cleavage rate on Day 3, blastocysts rate, or highquality blastocyst rate between CPM carriers and patients with normal chromosomes.…”
Section: Discussioncontrasting
confidence: 77%
“…Madon and Athalye (2005) showed that CPM accounts for a high proportion of patients with primary infertility or repeated miscarriages. Some studies show that CPMs are independently associated with multinucleated embryo formation (Sun et al, 2018). It is even suggested that male CPMs are linked to a higher cumulative early miscarriage rate and lower live birth rate following in vitro fertilization (IVF) (Ni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Without a reference standard other than between homologues, it is difficult to determine whether two similar-sized homologues are slightly smaller or larger than the normal ones [16]. In addition, we found that the diagnostic criteria in different literatures were not uniform, although most of the literature was consistent with ours [8, 17], some did not mention the details of the judgment criteria [9, 18]. This could be one of the reasons for conflicting reports of heteromorphisms impact human reproduction.…”
Section: Discussionsupporting
confidence: 71%
“…Finally, a previous study found that chromosomal polymorphisms were independently associated with the formation of multinucleated embryos . Of note, the good quality embryos rate in the multinucleated embryo group was lower than that recorded in the normal embryo group, which suggested that the good quality embryos rate might also be affected by semen quality.…”
Section: Discussionmentioning
confidence: 84%